Influence of Nitrogen Laser Irradiation on the Structural Properties of Nanocrystalline In2O3 Films Prepared by Chemical Spray Pyrolysis (Journal of the College of Basic Education, 2022)
In this research we study the influence of nitrogen laser N2 irradiation at( 337 nm) on the structural properties of nanocrystalline In2O3 Films with different power average (0.85, 1.70, 2.125 mW ) for irradiation time 5minute. By XRD technique, it was found that the structure of the as deposited thin films was polycrystalline, different peaks corresponds to (211), (222), (411), (420), (422), (521),(622), and (156), with a preferred orientation along (222) direction, the nitrogen laser irradiation leads to increase the intensity of these peaks and increase the full width at half maxima which leads to a decrease in the average grain size.